The White Indians of Mexican Cinema Racial Masquerade throughout the Golden Age - Garcia Blizzard, Mónica (SUNY series in Latin American Cinema, 2022)
The White Indians of Mexican Cinema theorizes the development of a unique form of racial masquerade-the representation of Whiteness as Indigeneity-during the Golden Age of Mexican cinema, from the 1930s to the 1950s. Adopting a broad decolonial perspective while remaining grounded in the history of local racial categories, Mónica García Blizzard argues that this trope works to reconcile two divergent discourses about race in postrevolutionary Mexico: the government-sponsored celebration of Indigeneity and mestizaje (or the process of interracial and intercultural mixing), on the one hand, and the idealization of Whiteness, on the other. Close readings of twenty films and primary source material illustrate how Mexican cinema has mediated race, especially in relation to gender, in ways that project national specificity, but also reproduce racist tendencies with respect to beauty, desire, and protagonism that survive to this day. This sweeping survey illuminates how Golden Age films produced diverse, even contradictory messages about the place of Indigeneity in the national culture.This book is freely available in an open access edition thanks to TOME (Toward an Open Monograph Ecosystem)-a collaboration of the Association of American Universities, the Association of University Presses, and the Association of Research Libraries-and the generous support of Emory University and the Andrew W. Mellon Foundation. Learn more at the TOME website, available at: https://www.openmonographs.org/. It can also be found in the SUNY Open Access Repository at: http://hdl.handle.net/20.500.12648/7153